Halal Fashion E-Commerce: Driving Social Inclusion in Peureulak - Mutia Nanda; Anis Kurlillah; Ade Fadillah FW Pospos; Muhammad Amin; Zulhilmi; Osman Abulkalam Fazal Ahmed (Muslim Business and Economics Review, 2025)
This study investigated the effectiveness of e-commerce in boosting halal fashion sales in Peureulak, Aceh, Indonesia, exploring its potential to enhance economic opportunities in the region. Employing a qualitative field research approach, data was gathered through interviews with key informants, including owners, employees, and buyers of halal fashion businesses in Peureulak. The research examined online strategies and their impact on sales. The findings revealed that e-commerce significantly increased halal fashion sales in Peureulak by expanding market reach beyond local boundaries and facilitating effective promotion and clear product information dissemination. Key success factors included ease of online access, high-quality product presentation, competitive pricing, trustworthy customer service, diverse payment options like Cash on Delivery (COD), and positive customer reviews. While local sales remained primarily conventional, e-commerce successfully attracted external customers, substantially supporting business growth. The study suggests that optimizing digital platforms like TikTok, Shoppe, and Instagram, alongside prioritizing rapid customer service, attractive promotions, and reliable product quality, are crucial strategies for enhancing e-commerce effectiveness in the halal fashion sector. These findings highlight the potential of e-commerce to drive economic growth and broader social inclusion within similar contexts in OIC countries by leveraging local strengths and expanding market access.